Histological findings following the use of a space-making device for bone reformation and implant integration in the maxillary sinus of primates - Cricchio, Giovanni; Palma, Vinícius Canavarros; Faria, Paulo E. P.; Oliveira, José Américo de [UNESP]; Lundgren, Stefan; Sennerby, Lars; Salata, Luiz A. (Wiley, 2009)
Background: Previous studies have shown that membrane elevation results in predictable bone formation in the maxillary sinus provided that implants can be placed as tent poles. In situations with an extremely thin residual crest which impairs implant placement, it is possible that a space-making device can be used under the sinus membrane to promote bone formation prior to placement of implants. Purpose: The present study was conducted to test the hypothesis that the use of a space-making device for elevation of the sinus membrane will result in predictable bone formation at the maxillary sinus floor to allow placement of dental implants. Materials and Methods: Eight tufted capuchin primates underwent bilateral sinus membrane elevation surgery, and a bioresorbable space-making device, about 6 mm wide and 6 mm in height, was placed below the elevated membrane on the sinus floor. An oxidized implant (Nobel Biocare AB, Gothenburg, Sweden) was installed in the residual bone protruding into the created space at one side while the other side was left without an implant. Four animals were sacrificed after 6 months of healing. The remaining four animals received a second implant in the side with a space-making device only and followed for another 3 months before sacrifice. Implant stability was assessed through resonance frequency analysis (RFA) using the Osstell™ (Osstell AB, Gothenburg, Sweden) at installation, 6 months and 9 months after the first surgery. The bone-implant contact (BIC) and bone area inside the threads (BA) were histometrically evaluated in ground sections. Results: Histologically there were only minor or no signs of bone formation in the sites with a space-making device only. Sites with simultaneous implant placement showed bone formation along the implant surface. Sites with delayed implant placement showed minor or no bone formation and/or formation of a dense fibrous tissue along the apical part of the implant surface. In the latter group the apical part of the implant was not covered with the membrane but protruded into the sinus cavity. Conclusions: The use of a space-making device, with the design used in the present study, does not result in bone formation at the sinus floor. However, membrane elevation and simultaneous placement of the device and an implant does result in bone formation at the implant surface while sites with implants placed 6 months after membrane elevation show only small amounts of bone formation. It is suggested that lack of stabilization of the device and/or a too extensive elevation of the membrane may explain the results. © 2009, Wiley Periodicals, Inc.
Keywords: Bone formation; Dental implants; Maxillary sinus; Membrane elevation; Osseointegration; polyester; polylactide; animal; bone development; bone regeneration; Cebidae; instrumentation; male; maxillary sinus; nose mucosa; oral surgery; tooth implantation; tooth prosthesis; vibration; Animals; Cebus; Dental Implantation, Endosseous; Dental Prosthesis Retention; Male; Maxillary Sinus; Nasal Mucosa; Oral Surgical Procedures, Preprosthetic; Osteogenesis; Polyesters; Vibration